A Legal Review of the Natuna Sea Dispute Between Indonesia and China in International Law - Afrian Tama Syahputra; Diki Zukriadi (Jurnal Multidisiplin Sahombu, 2025)
This article aims to analyze the ongoing negotiations between Indonesia and China regarding the Natuna Islands from the perspective of international law. As a maritime nation comprising over 17,000 islands, Indonesia possesses vast territorial waters and abundant natural resources, including fisheries, minerals, and hydrocarbons. These assets render territorial disputes inevitable, particularly in contested maritime zones. The Natuna Islands, located in the northern part of Indonesia's exclusive economic zone (EEZ), have emerged as a focal point of contention with China, whose expansive claims in the South China Sea overlap with Indonesia's sovereign rights. The dispute stems from China's assertion of historical rights over the South China Sea, encapsulated in its "nine-dash line," which Indonesia rejects as incompatible with the United Nations Convention on the Law of the Sea (UNCLOS). Under UNCLOS, coastal states like Indonesia are entitled to an EEZ extending up to 200 nautical miles, encompassing rights to exploit resources and enforce jurisdiction. Incidents, such as Chinese fishing vessels entering Indonesian waters in 2016, have escalated tensions, prompting diplomatic protests and military patrols. These clashes highlight the broader geopolitical rivalry, where China's Belt and Road Initiative intersects with Indonesia's strategic interests. The ramifications of this unresolved dispute are multifaceted. Economically, it fosters instability by deterring foreign investment in resource-rich areas like the Natuna's oil fields, potentially costing billions in lost revenue. Globally, it contributes to polarization, exacerbating divisions between Western-aligned nations and those like China, while straining ASEAN unity. Politically, it undermines Indonesia's domestic stability, fueling nationalist sentiments and social unrest amid rising populism. Socially, it burdens communities dependent on maritime livelihoods, exacerbating issues like illegal fishing and environmental degradation. In light of these consequences, a peaceful resolution is imperative. Pursuing such an outcome could enhance economic prosperity through collaborative oil exploration, ensuring equitable resource sharing under international oversight. Improved border monitoring and management, facilitated by joint patrols or technology transfers, would mitigate incursions and foster trust.